Development planning ; lessons of experience - Waterston, Albert; Martin, C.J. (Baltimore ; Johns Hopkins Press, 1965)
The book is a comparative study of development planning. It attempts to identify when, how and why planning has been successful and unsuccessful, and to draw relevant lessons of experience therefrom.
Includes index.
Includes bibliographical references: p. 660-681.
gp 21/01/2019
Loans
Keywords: Economic policy; Economic history